An unusual cause of Grade IIIb Clavien complication of percutaneous nephrolithotomy: Broken and retained Malecot nephrostomy catheter - Ozveren, Bora; Sahin, Ahmet (Canadian Urological Association Journal, 2016)
Percutaneous nephrolithotomy (PCNL) is a relatively safe operation with low rates of major complications. Clavien-Dindo classification is a validated system to record complications, although still needing standardization in reporting and scoring of complex and rare events. We report an unusual adverse incident that required interventional management and impacted the postoperative course. The case of a broken re-entry Malecot nephrostomy catheter as it was being removed on the third postoperative day of an otherwise uneventful PCNL is described. The retained part was removed by open-surgery under general anesthesia. This incident has upgraded the minimally invasive surgery to a Grade IIIb complicated procedure according to the modified Clavien classification. Patient data, procedure conditions, and surgical retrieval of the catheter are detailed. Although far from being life-threatening, this rare complication due to a broken and retained drainage catheter is regarded as a high-grade complication according to the Clavien system.